Energy-Efficient Office Renovation - Minyoung KWON (A+BE: Architecture and the Built Environment)
This research aims to develop user-focused design principles for energy-efficient office renovations. The goal of this is to improve the quality and comfort of workspaces without compromising on energy-saving goals. Due to increasing sustainability requirements, new ways of working and changing office user preferences, there is a growing need for office renovations that not only deal with the energy performance and the replacement of building facilities, but also the occupants’ health and well-being. The renovation of office buildings can substantially reduce energy demand and improve building performance. For this reason, most studies regarding office renovations have focused on achieving better energy performance and indoor environmental quality. Also, several studies have investigated employee satisfaction in the work environment. However, the users are only considered after the buildings have been built and taken into use (e.g., postoccupancy evaluation), but not in the early stage of the design phase. Although there are building regulations and norms regarding indoor comfort, no clear design principles or guidelines considering users have been developed for office renovations. Therefore, it is necessary to explore how office users can be included in the early design stage of office renovations to improve their comfort and satisfaction. This led to the following main research question to be answered in this thesis: